Impact of a Stroke Network in Mexico to Achieve Successful Revascularization Even in Elderly Patients (Revista de Medicina Clinica, 2022)
Introduction: Cerebral vascular disease (CVD) affects approximately 12.2 million people per year, it is the third leading cause of death and disability combined worldwide. In Mexico there was no organized stroke care network within the public health system, in order to offer different reperfusion therapies in 2019 we integrated the first network in the Mexican public health system called ResISSSTE Cerebro. Cases Reports: Case 1 - 95-year-old woman with acute cerebral infarction, arrived 2.5 hours after the onset of symptoms at an essential center (EC) of the network, was transferred at 5.5 hours to the AC at a distance of 3.3 km, the NIHSS (National Institutes of Health Stroke Severity Scale) at admission was 21 points, mechanical thrombectomy (MT) with Rankin 1 was performed at discharge and at 90 days. Case 2 - 95-year-old woman with acute cerebral infarction, arrived 60 minutes later at a network CE, moved to the AC at a distance of 103 km at 4.3 hours with 10-point NIHSS, TIV and TM were performed with NIHSS post-treatment of 1 point and Rankin 1 at 30 and 360 days. Conclussion: In low-middle income countries (LMIC) there are many barriers to stroke care, so organized stroke care networks must be built that allow access to basic and advanced imaging studies that are necessary for the evaluation of patients. requiring cerebral reperfusion therapy, without excluding patients over 80 years of age.
Keywords: ischemic stroke; Stroke; Thrombolysis; Thrombectomy